Behaviour of ultra high performance concrete wall panels under two-way in-plane loading. (1st January 2014) - Ganesan, N.; Abraham, Ruby; Beena, P.R.; Thomas, Anisha
This paper presents the results of an experimental investigation conducted to determine the behaviour of ultra high performance concrete (UHPC) wall panels under two-way in-plane loading. Strength and behaviour of nine square wall panels of size 500 × 500 mm, 750 × 750 mm and 1, 000 × 1, 000 mm, supported on all the four sides, were evaluated. The panels were subjected to uniformly distributed load applied at a small eccentricity of t/6, where 't' is the thickness of wall panel, to reflect possible eccentric load in practice. The effect of slenderness ratio was studied by keeping the aspect ratio constant. Slenderness ratios selected were 14.3, 21.4 and 28.6. The results indicate that the increase in slenderness ratio increases the deflection and decreases the axial strength ratio of wall panels. The ultimate loads obtained from experimental study were also compared with those predicted by equations available in literature for wall panels under two-way in-plane action.